Efficacy of Cryoablation on Chronic Rhinitis Management: A Systematic Review and Meta-Analysis. Issue 4 (July 2023) - Young, Kurtis; Bulosan, Hannah; Kejriwal, Sameer; Liang, Jonathan; Wu, Arthur W.; Tang, Dennis M.; Birkeland, Andrew C.; Steele, Toby O.
Background: ClariFix for posterior nasal nerve ablation has been approved for use since 2017, and this is the first study attempting to synthesize and assess the efficacy of this new device on the management of chronic rhinitis. Objective: The primary objective of this meta-analysis is to assess the efficacy of ClariFix in the symptomatic management of patients with chronic rhinitis. The main outcome measure is the mean difference in the reflective total nasal symptom score (rTNSS). Methods: A systematic search of Pubmed/Medline, Web of Science, and EBSCOhost was conducted from inception to May 2022. Peer-reviewed clinical trials reporting postcryotherapy rTNSS at both 1- and 3-month intervals for patients with chronic rhinitis were included. A random-effects model was utilized for meta-analysis. Study heterogeneity, bias, and overall quality were all assessed. The authors followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. The primary outcome measures included mean differences in rTNSS from baseline to both 1- and 3-month postoperative time points. Secondary measures included other questionnaires including the Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ). Results: There were 5 studies that met the criteria (247 individuals). The pooled rTNSS mean difference from baseline to 1 and 3 months postoperatively was found to be −3.48 points (95% CI: −3.73 to −3.23, I 2 = 0.13). and −3.50 (95% CI: −3.71 to −3.29, I 2 = 0.00), respectively. The mean difference from baseline to 3 months postoperatively regarding the RQLQ was found to be −1.53 (95% CI: −1.74 to −1.31, I 2 = 0.00). The most common adverse effects included facial or surgical site pain (40.4%), followed by headache (18.2%), oral numbness (11.1%), and sinusitis (4.0%). Conclusions: The findings of this systematic review suggest that cryoablation with Clarifix is an effective treatment modality for chronic rhinitis. However, higher-quality randomized controlled trials will need to be performed to affirm the findings of this study.